The Influence of Father’s Parenting Practices, Self-Control, and Problematic Social Media Use on Mental Health Generation Z - Fajria, Khanifa; Hastuti, Dwi; Riany, Yulina Eva (International Journal of Public Health Excellence (IJPHE), 2025)
Social media has become an inseparable part of many people's daily lives. Increasing concerns have arisen regarding its negative impact on users’ mental health. This study aims to identify and examine the influence family and Generation Z characteristics, father’s parenting practices, self-control, problematic social media use, and mental health among Generation Z. The research was cross-sectional study design with purposive sampling. The study involved participants born between 1997 to 2012 (Generation Z), social media active users and still had a living father, whether living in the same household or separately. A total of 208 respondents participated in the study. Both primary and secondary data were used. Primary data were collected through interviews using questionnaires, while secondary data were obtained through literature reviews and previous research findings. The results showed that self-control had a significant negative effect on both problematic social media use and mental health. Furthermore, father’s parenting practices have a significant negative influence on self-control and mental health. It is recommended that families with Generation Z children enhance their literacy and understanding of effective parenting practices. Fathers are also encouraged to take an active role in the parenting process to support the psychological and psychosocial well-being of Generation Z